Antecedentes e dimensões do engajamento dos usuários de redes sociais: um estudo com o facebook - Bruno Brito Pereira de Souza (2012)
The classical view of customer management considers customers to be an exogenous component of firms value creation activities. However, a different perspective is now emerging. A central aspect of this new perspective is the concept of Customer Engagement. Engagement refers to the creation of a more profound and significant connection between thefirm and the consumer which lasts over time. Also noteworthy is the fact that parallel to the interest in studying Customer Engagement, the increasing use of the Internet has caused the proliferation of social networking sites such as Facebook, YouTube, Google+, LinkedIn,Twitter and Instagram, which have allowed Internet users to extend the scope of their connections with others. This study aimed to measure Customer Engagement with the Facebook social network. Concepts and characteristics of the Society and Culture of Consumption, Web 2.0 and Social Media were also explained. The operationalized model consisted of the engagement antecedents [Satisfaction, Trust, Commitment, Moral Identity, Consumption Goals, Resources Available and Perceived Costs/Benefits] proposed by Van Doorn et al. (2010), the antecedent [Psychographic Similarity] proposed by Almeida et al. (2011) and the antecedent [Customer Orientation] proposed by Narver and Slater (1990). Customer Engagement was operationalized as a reflective second-order construct formed by the dimensions [Customer Lifetime Value, Customer Referral Value, Customer Influencer Value and Customer Knowledge Value] proposed by Kumar et al. (2010). The research was carried out in two stages. The first stage, using one online focus groups, was exploratory and qualitative in nature. The second step was of the quantitative type using a survey that made it possible to describe the experimental situation and draw conclusions about it. 744 questionnaires were collected, and were tabulated and analyzed using the SPSS, AMOS and SmartPLS statistical programs. The contributions of this research to Academia were: operationalization of the Customer Engagement antecedents proposed by Van Doorn et al. (2010), operationalization of Customer Engagement in four dimensions as proposed by Kumar et al. (2010), putting forward two other antecedents of Customer Engagement in the context of social networks and quantitative analysis of the proposed model using two structural equation programs (AMOS and SmartPLS). The constructs Moral Identity (Customers Own Behavior and Behavior of Other Participants) and Consumption Goals (Social Aspects and Financial Aspects) have two dimensions. The modeling that used the AMOS program resulted in the validation of the constructs Satisfaction, Psychographic Similarity, Available Resources, Perceived Costs/Benefits, Customer Orientation, and Moral Identity - Behavior of Other Participants as antecedents of Customer Engagement. With the exception of Satisfaction and Trust, all constructs were validated as antecedents of Customer Engagement in the modeling that used the SmartPLS program. The hypothesis that Customer Engagement with Facebook is a reflective second-order construct was partially supported by the results obtained from the AMOS program, therefore the dimensions Customer Referral Value and Customer Influencer Value did not show discriminant validity and have been grouped. However, the results from the SmartPLS program, did support this hypothesis. The operationalized antecedents explained 40% (AMOS) and 55% (SmartPLS) of the Customer Engagement variation. The model showed good quality of fit and almost full validation of the scales used.